2016
DOI: 10.1038/srep32286
|View full text |Cite
|
Sign up to set email alerts
|

Residual Tumor Volume as Best Outcome Predictor in Low Grade Glioma – A Nine-Years Near-Randomized Survey of Surgery vs. Biopsy

Abstract: Diffuse low grade gliomas (DLGG) are continuously progressive primary brain neoplasms that lead to neurological deficits and death. Treatment strategies are controversial. Randomized trials establishing the prognostic value of surgery do not exist. Here, we report the results of a nine-year near-randomized patient distribution between resection and biopsy. Until 2012, the Department of Neurosurgery and the Department of Stereotactic Neurosurgery at the University Medical Center Freiburg were organized as separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 41 publications
4
57
2
2
Order By: Relevance
“…Since the existing literature is a mix of progression and transformation, the numbers would likely differ even 19 (44) more between astrocytomas and oligodendrogliomas if only malignant transformation was analyzed. In the surgical literature several studies have reported that remnant less than 10-15 ml have a better prognosis [36,37] although no visible postoperative remnant is clearly superior [38][39][40]. In our series, smaller residual tumor volumes than 10 ml did not protect against transformation although it was seen in only 7% of cases.…”
Section: Tumor Burdencontrasting
confidence: 53%
“…Since the existing literature is a mix of progression and transformation, the numbers would likely differ even 19 (44) more between astrocytomas and oligodendrogliomas if only malignant transformation was analyzed. In the surgical literature several studies have reported that remnant less than 10-15 ml have a better prognosis [36,37] although no visible postoperative remnant is clearly superior [38][39][40]. In our series, smaller residual tumor volumes than 10 ml did not protect against transformation although it was seen in only 7% of cases.…”
Section: Tumor Burdencontrasting
confidence: 53%
“…Another criticism we faced was that the cohort from region A did so poorly that they could not be representative for a LGG cohort, but this speculation is refuted after molecular classification. In fact, survival in region A compares well to historical Surveillance, Epidemiology, and End Results (SEER) data from the years before extensive surgery was as often attempted or achieved and from other studies studying biopsies as a surgical policy [ 22 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 73%
“…Retrospective uncontrolled studies report a clear advantage with radiological complete resection, although often not achievable [ 3 , 4 , 21 ]. Others have emphasized that a residual tumor volume <15 ml must be achieved to have a beneficial survival effect [ 22 ]. However, extent of resection is not random and selection bias may clearly be an issue in such studies.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 1 subgroup of 5 patients who underwent subtotal resection and died rapidly-that is, at a median time from radiological diagnosis of 3.5 years-while OS in patients with WHO grade II gliomas who benefited from early (sub)total resection was 14-15 years in recent surgical series. 6,22,29,34 However, in a second subgroup, none of the 21 patients with a long-term followup over 5 years died (including 2 patients who underwent surgery more than 10 years ago). Thus, the 5-year survival rate is 77.27%.…”
Section: Discussionmentioning
confidence: 99%